The effect of individuals' oral hygiene habits and knowledge levels on peri-implant health and disease: a questionnaire-based observational study - Tuğba Şahin (BMC, 2024)
Abstract Background Peri-implant disease and health are associated with microbial dental plaque. Therefore, oral hygiene plays a role in preventing and treating these diseases. This study aimed to determine the relationships among knowledge of peri-implant status, oral hygiene habits, and peri-implant disease and health. Methods A total of 144 implants in nonsmokers with controlled systemic disease were included in the study. Peri-implant disease and the conditions of the implants were determined with periodontal indices and radiographs based on the 2017 World Workshop on the Classification of Periodontal and Peri-implant Diseases and Conditions and The EFP S3 level clinical practice guideline. Individuals were asked 66 questions regarding demographic information, oral hygiene habits and history, and knowledge of peri-implant diseases. One-way ANOVA was used to compare the three peri-implant disease and condition categories. Results There was a significant difference between groups regarding toothpaste type (p < 0.05). Gum protection toothpaste was greater in the peri-implant health group. Patients' use of interdental products was very low; often, no products were used for implant prosthesis. There was no significant difference among the groups regarding oral hygiene product use or oral hygiene habits (p > 0.05). There was a significant difference between groups regarding frequency of visit (p < 0.05). The frequency of visits to the dentist for pain was greater for individuals with peri-implantitis. There is a significant difference between the groups' answers for the causative and initiating factors of peri-implant disease (p < 0.05). The peri-implant health group answered that microbial dental plaque is the most crucial initiating factor of peri-implant diseases, and bleeding on probing is the most critical determinant of peri-implant diseases at a higher rate than the other groups. Conclusions Patients' oral hygiene habits and knowledge levels are almost similar according to peri-implant status. Knowledge does not reflect a patient's oral hygiene behavior. Clinicians should ensure that individuals' oral hygiene practices align with their increased awareness regarding peri-implant illnesses.